Mixed serous and mucinous retroperitoneal cystadenoma: an extremely rare case. Issue 11 (11th November 2021) - Khan Hotak, Mirwais; He, Mike
Abstract: Mixed serous and mucinous retroperitoneal cyst adenoma is an extremely rare condition as most of the reported cases in the literature are primary retroperitoneal mucinous cystadenomas and primary retroperitoneal serous cystadenomas. They are initially asymptomatic and become symptomatic gradually depending on their size and anatomical extension and location. We report a 49-year-old woman with a history of right-side abdomen pain for a few years. Diagnostic images revealed a large retroperitoneal cystic lesion. A laparoscopic resection was performed without spillage. The patient was discharged without complication postoperatively and no recurrence on follow-up. Surgical excision, either open/or laparoscopic without any spillage, remains the most effective and appropriate treatment for this lesion.